Ray Casting With ?On-the-Fly? Region Growing 3-D Navigation Into Cardiac MSCT Volume. - Coatrieux, J.-L.
This paper describes an extended ray casting scheme for three-dimensional (3-D) navigation into the heart cavities for preoperative planning using multislice X-ray computed tomography data. The key benefit is that artifacts due to contrast inhomogeneities can be eliminated during volume traversal, thus improving the visual perception of the endocardial wall
Keywords: 3-D navigation; Cardiac MSCT volume; Cardiac resynchronization therapy; Endocardial wall; Extended ray casting scheme; Heart cavities; Multislice X-ray computed tomography data; Preoperative planning; Three-dimensional rendering; Virtual navigation; Visual perception; Volume traversal